Analisis Personality, Burnout Syndrome dan Gaya Kepemimpinan Transformasional terhadap Kinerja Pegawai Melalui Motivasi Kerja sebagai Variabel Intervening di Dinas Pendidikan Pemuda dan Olahraga Kabupaten Bantul - Muhamad Nasrip; Kusuma Chandra Kirana; Syamsul Hadi (LPPM Institut Nasional Laa Roiba Bogor, 2023)
This study entitled the analysis of personality, burnout syndrome and transformational leadership style on employee performance through work motivation as an intervening variable in the education, youth and sports office of Bantul Regency. The research method uses quantitative methods. The population is 215 people with 138 samples. The analysis tool uses a path analysis model using the SmartPLS 3.3.3 application. from the results of the analysis it can be concluded that: a) Personality has a positive and significant influence on work motivation; b) Burnout Syndrome has a significant and significant effect on work motivation; c) Transformational Leadership Style has a significant and significant influence on work motivation; d) Personality has no significant influence on Employee Performance; e) Burnout Syndrome has a significant and significant impact on Employee Performance; f) Transformational Leadership Style has a significant influence on employee performance; g) Work Motivation has a significant and significant influence on Employee Performance; h) Work motivation is proven to be able to play a negative role as an intervening variable for the influence of personality (X1) on performance (Y) of (-0.044) with a P-Value of 0.132; i) Work motivation is proven to be able to play a role as an intervening variable for the effect of burnout syndrome (X2) on employee performance (Y) of 0.275 with a P-Value of 0.030. j) Work motivation is proven to be able to act as an intervening variable, the effect of transformational leadership style (X3) on employee performance (Y) is 0.052 with a P-value of 0.111. Keywords: Personality, Burnout Syndrome, Transformational Leadership Style, Employee Performance, Work Motivation.